Sacral Neuromodulation: An Effective Treatment for Lower Urinary Tract Symptoms in Multiple Sclerosis. Issue 7 (July 2016) - Puccini, Federica; Bhide, Alka; Elneil, Suzy; Digesu, G. Alessandro
Abstract : (Abstracted from Int Urogynecol J 2016;27:347–354) Approximately 80% of patients with multiple sclerosis (MS) have lower urinary tract symptoms (LUTSs), which have a major impact on quality of life. The most common urodynamic abnormalities include neurogenic detrusor overactivity, detrusor underactivity, and detrusor sphincter dyssynergia.